Fall sensors, home emergency system, and social service for ≥ 75-year-olds living at home - a matched control intervention study - Jan C. Zoellick; Sonia Lech; Julie L. O’Sullivan; Eva Jansen; Juliana Supplieth; Ronny Kuhnert; Ulrike Grittner; Johanna Schuster (BMC Geriatrics)
Abstract Background Medical emergencies occur frequently at home and during leisure activities. Digital technologies hold great potential for novel approaches towards emergency detection and treatment. The purpose of this study was to evaluate an integrated home-based emergency call system. Methods We conducted a matched-control intervention study with 180 participants (M: 81.7 years; SD: 4.1 years; 68% female) in the intervention group (IG) and 708 matched controls (M: 81.4 years; SD: 3.9 years; 68% female). The intervention targeted ≥ 75-year-old community-dwelling adults and consisted of a base station, motion sensors for the home, a necklace with fall detection sensors, and a social service. We expected fewer emergency contacts and fewer hospitalisations in the IG than in the control group (CG). Secondary outcomes were healthcare costs and subjective assessments by participants. Negative binomial regression models and linear regression analyses were used to test the primary and secondary hypotheses. Results Our results revealed similar rates of emergency contacts (IRR = 0.89 [95%-CI:0.62–1.28]; p = .523) and hospitalisations (IRR = 1.23 [95%-CI:0.95–1.60]; p = .122) with similar durations (MDiff = -2.79 days [95%-CI:-7.63–2.06]; p = .260) and similar healthcare costs (-7%, [95%-CI: -54%-40%], p = .774) in the IG compared to matched controls (intention to treat approach). Regarding changes in the IG over time, participants reported worse subjective outcomes, e.g., lower health-oriented quality of life (Mt0 = 40.4; SDt0 = 8.7; Mt1 = 37.6; SDt1 = 8.0; t(124) = -4.10; p ≤ .001) at the end of the 12 months intervention period compared to the beginning of the study. Conclusions The intervention had no effect on hospitalisations and emergency contacts. However, participants made also little use of the intervention. The observed decline in subjective health and other subjective outcomes may be attributed to the high age of participants at intervention start and overall circumstances due to the COVID pandemic. The market for technologies for older adults is highly dynamic and growing quickly; thus, more suitable and effective technologies might be developed soon. These novel technologies should be evaluated accordingly before entering the market. Trial registration DRKS00023171 ( https://drks.de/search/en/trial/DRKS00023171 ).